EXPRESSIVE THERAPIES CONTINUUM-INFORMED EVALUATION OF THREE RESOURCE-ORIENTED RECEPTIVE AND ACTIVE MUSIC THERAPY TECHNIQUES IN CANCER PATIENTS IN PSYCHOSOCIAL REHABILITATION PROGRAMME - Duhovska, Jana; Millere, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Expressive Therapies Continuum (ETC), a model posed by Lusebrink and widely used in arts therapies, stipulates that human being is perceiving the world and processing the information in three modes – motion (kinesthetic-sensory perception), emotion (perceptual-emotional perception) and thought (cognitive-symbolic perception), and that optimally functioning person can freely function in all the modes, can slide between the poles of each of the mode and can integrate the elements from various modes and poles. And vice versa - difficulty or inability to function or being stuck in certain modes, can indicate to malfunction and even psychopathology. If that is the case - purposeful integration of various functions by offering expressive activity promoting utilisation of various functions of the ETC, can promote the optimal functioning. In order to find out the capacity of the three resource-based music therapy activities – 1) receptive music therapy activity, 2) semi-structured musical improvisation, 3) song-writing activity - to stimulate the utilisation of specific levels and polarities of the ETC, participants (n=24 cancer patients participating in the psychosocial rehabilitation programme) were asked to assess the elements of the ETC they applied while executing each of the activities. Results of the study show that during the receptive music therapy activity participants mostly used the affective, symbolic and sensory function, during the song-writing activity the mostly used all ETC functions except for sensory, but musical improvisation provoked application of all the ETC functions, and therefore turned out as ultimate activity, capable of integrating all the modes of perception and information processing.